Tropy akowskie w poezji Jerzego Ficowskiego - Kandziora, Jerzy (My University, 2012)
The article presents the evolution of the theme of Armia Krajowa (Home Army) and the Warsaw Uprising, in Ficowski’s poetry. The theme, engaged by the poet in the late 1940s (Ołowiani żołnierze, 1948), was quickly abandoned as incompatible with the imaginary, magical direction in the development of young Ficowski’s poetry. Neither was the theme fostered by the general political background of the “dead season” of Communist Poland, by censorship, and by Ficowski’s fear of settling for the post-Romantic stereotype and patriotic myth-making. The theme returned in the 1970s (Gryps, 1979; Errata, 1981), which was related to Ficowski’s decision to liberate himself from self-censorship, and his readiness to express the once repressed content in his own, mature poetic idiom. The present study presents two aspects of historical narration in the Home-Army poems from the 1970s: the fabulous quality, which positions history in Ficowski’s private topics and intimate memory, and the scientific, naturalistic quality, which relates history to physical and cosmic categories. Both aspects redeem the poetry from the narrow specificity of Polish national myth, and make it possible to reconcile individual truth of the experience of death and suffering with the discourse of concepts and historiosophy, which also touches upon the cosmic order.
Home Army in the Poetry of Jerzy Ficowski
Keywords: Jerzy Ficowski; poetry; themes and motifs; war; Warsaw Uprising; Home Army (Armia Krajowa); fable; private topos; neopositivism; cosmos; historical narration